1990
DOI: 10.1073/pnas.87.17.6664
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymerases alpha, delta, and epsilon: three distinct enzymes from HeLa cells.

Abstract: DNA polymerases a, 8, and e have been purified and characterized from the same HeLa cell extract in order to determine their relationship by comparing them from the same cell type. The catalytic properties and the primary structures of the large subunits of the DNA polymerases as compared by partial peptide mapping with N-chlorosuccinimide are different. Likewise, the small subunit of DNA polymerase e appears to be distinct from the large subunit of the same polymerase and from the smaller subunits of DNA poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
96
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(100 citation statements)
references
References 33 publications
4
96
0
Order By: Relevance
“…Earlier skepticism that Pol d was simply Pol a contaminated with a 3 0 -5 0 exonuclease activity was dispelled by the demonstration that both the polymerase and exonuclease activities were associated with the p125 catalytic subunit [Lee et al, 1980;Lee et al, 1984]. A second form of ''Pol d'' with a larger catalytic subunit was discovered and is now known as Pol e [Syvaoja et al, 1990;Pospiech and Syvaoja, 2003;Pursell and Kunkel, 2008]. Molecular cloning of p125 showed that the catalytic core was highly conserved in evolution from T4 bacteriophage to human Hao et al, 1992;Yang et al, 1992], and Pol d is now classified as a member of the B family polymerases.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier skepticism that Pol d was simply Pol a contaminated with a 3 0 -5 0 exonuclease activity was dispelled by the demonstration that both the polymerase and exonuclease activities were associated with the p125 catalytic subunit [Lee et al, 1980;Lee et al, 1984]. A second form of ''Pol d'' with a larger catalytic subunit was discovered and is now known as Pol e [Syvaoja et al, 1990;Pospiech and Syvaoja, 2003;Pursell and Kunkel, 2008]. Molecular cloning of p125 showed that the catalytic core was highly conserved in evolution from T4 bacteriophage to human Hao et al, 1992;Yang et al, 1992], and Pol d is now classified as a member of the B family polymerases.…”
Section: Introductionmentioning
confidence: 99%
“…Although the 3'?5' exonuclease activity of the wt p53 protein might provide a biochemical basis for the direct involvement of this molecule in the repair of certain types of DNA damage, the biological relevance of this enzyme activity remains elusive. The observations that p53 protein is co-localized with the DNA replication machinery (Gannon and Lane, 1987;Cox et al, 1995) and that mammalian DNA pol a, unlike pol d and pol e, lacks the 3'?5' exonuclease activity for proofreading (Syvaoja et al, 1990;Bambara and Jessee, 1991) provide hints that link p53 with DNA replication ®delity. Because the misincorporation of non-complementary nucleotides during DNA replication represents a major mechanism of gene mutation, prompt removal of the misincorporated nucleotides from DNA is critical for genomic stability.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it has been shown that SV40 DNA replication is also pol ⑀-independent (23), but this polymerase might be required for the chromosomal DNA replication in vivo (33). It has been shown that pol ⑀ is one of the replicative polymerases in HeLa cells (35). Studies from several laboratories suggest that pol ⑀ is involved in the cell cycle checkpoint control and may function to ensure accurate DNA synthesis (31, 34, 70, 71).…”
Section: Figmentioning
confidence: 99%
“…Unlike pol ␦, the role of pol ⑀ remains unclear. Pol ⑀ is a highly processive enzyme that has been implicated in the genomic DNA replication, DNA repair, recombination, as well as the S phase checkpoint control (31)(32)(33)(34)(35)(36).…”
mentioning
confidence: 99%